School choice, school costs: the case of inner city Johannesburg private schools - Machard, Deborah; McKay, Tracey Morton (Acta Academica: Critical views on society, culture and politics, 2015)
This study explores school choice and school commuting within the City of Johannesburg, with specific reference to enrolment in low cost inner city private high schools. The study found that the majority of learners enrolled in these schools were black and hailed from upper working class or lower middle class homes. Although most commuted to school, the schools also serve a resident inner city community. That is, private school enrolment is partly due to the changing land use patterns of the Johannesburg inner city, from residential to commercial. While much of the inner city has been transformed into housing, there has been no provision of essential social infrastructure such as public schools, leaving residents with little choice but to enrol in a private school, despite their low incomes. Learners from peripheral areas such as Soweto and Alexandria embark on a financially and socially costly school commute in order to access what they perceive to be quality education. That is, parents perceive these schools to be good academic performers, to be ‘disciplined’ and to offer quality teaching. These parents are shunning the no-fee, public township schools, deeming them dysfunctional and poorly resourced. It does appear that access to quality education in South Africa is becoming linked to ability to pay school fees – not only for the wealthy but also for those of lower socio-economic status.